Integration and Encapsulation of Light-Emitting Diode and CMOS-MEMS Chips for Fluorescence Quenching Gas Sensor - Lee, Ya-Chu; Liou, Cheng-Shiun; Chien, Tung-Lin; Tsou, Chingfu; Fang, Weileun (Frontiers in Mechanical Engineering, 2022)
Environmental sensing units such as gas sensors, humidity sensors, pressure sensors, PM 2.5 sensors, or temperature sensors are widely used in our daily lives. In this study, the CMOS-MEMS technology is exploited to fabricate and monolithically integrate the photo-sensors, temperature sensor, and mechanical structures for the optical gas sensing chip. An LED is bonded (heterogeneous integration) on the CMOS-MEMS chip as a excitation light source, and the fluorescence quenching technology is employed for the presented optical gas sensor. Finally, the light emitted from the LED is reflected and redirected onto the CMOS-MEMS chip by an encapsulated optical reflector to increase the sensitivity and reduce the power consumption for the presented sensor. In applications, the sensing materials are respectively mixed with C30H24Cl2N6Ru·6H2O and C16H7Na3O10S3 for O2 and CO2 detections. Moreover, the Si-based (by micromachining) and polymer-based (by 3D printing) optical reflectors are used to encapsulate the sensing chip to demonstrate the presented concept. Measurements show that the LED driving currents for gas sensors with reflectors are significantly reduced. Measurements also indicate sensitivities of gas sensors are: for sensing chips without optical reflectors are respectively 0.023μA/% (O2/N2) and 0.12μA/% (CO2/N2); for sensing chips with hemispherical shell optical reflectors are respectively 0.12μA/% (O2/N2) and 0.19μA/% (CO2/N2); for sensing chips with flat plate optical reflectors are respectively 0.24μA/% (O2/N2) and 0.32μA/% (CO2/N2). The sensitivity of the temperature sensor is 0.07%/°C.